The Little Data Book on Information and Communication Technology 2017 - World Bank Group (Washington, DC: World Bank, 2016)
This Little Data Book on Information and Communications Technology 2017 presents tables for 217 economies showing the most recent national data on key indicators of information and communications technology (ICT), including access, quality, affordability, efficiency, sustainability, and applications.